Changes in Hemodynamic Response Function Resulting From Chronic Alcohol Consumption - Desmond, John E.; Rice, Laura C.; Cheng, Dominic T.; Hua, Jun; Qin, Qin; Rilee, Jessica J.; Faulkner, Monica L.; Sheu, Yi‐Shin; Mathena, Joanna R.; Wand, Gary S.; McCaul, Mary E. (Alcoholism, clinical and experimental research, 2020)
Background Functional MRI (fMRI) task‐related analyses rely on an estimate of the brain's hemodynamic response function (HRF) to model the brain's response to events. Although changes in the HRF have been found after acute alcohol administration, the effects of heavy chronic alcohol consumption on the HRF have not been explored, and the potential benefits or pitfalls of estimating each individual's HRF on fMRI analyses of chronic alcohol use disorder (AUD) are not known. Methods Participants with AUD and controls (CTL) received structural, functional, and vascular scans. During fMRI, participants were cued to tap their fingers, and averaged responses were extracted from the motor cortex. Curve fitting on these HRFs modeled them as a difference between 2 gamma distributions, and the temporal occurrence of the main peak and undershoot of the HRF was computed from the mean of the first and second gamma distributions, respectively. Results ANOVA and regression analyses found that the timing of the HRF undershoot increased significantly as a function of total lifetime drinking. Although gray matter volume in the motor cortex decreased with lifetime drinking, this was not sufficient to explain undershoot timing shifts, and vascular factors measured in the motor cortex did not differ among groups. Comparison of random‐effects analyses using custom‐fitted and canonical HRFs for CTL and AUD groups showed better results throughout the brain for custom‐fitted versus canonical HRFs for CTL subjects. For AUD subjects, the same was true except for the basal ganglia. Conclusions These findings suggest that excessive alcohol consumption is associated with changes in the HRF undershoot. HRF changes could provide a possible biomarker for the effects of lifetime drinking on brain function. Changes in HRF topography affect fMRI activation measures, and subject‐specific HRFs generally improve fMRI activation results. During functional MRI (fMRI) scanning, participants were cued to tap their fingers, and averaged hemodynamic response functions (HRFs) were extracted from the motor cortex. Excessive alcohol consumption was associated with changes in the timing of the HRF undershoot. HRF changes could provide a possible biomarker for the effects of lifetime drinking on brain function. Changes in HRF topography affect fMRI activation measures, and subject‐specific HRFs generally improved fMRI activation results.